ZnO nanostructures grown on vertically aligned carbon nanotubes by laser-assisted flow deposition - Rodrigues, J.
Nanoscale junctions between conductive and semiconductor materials, by promoting a large interfacial area, are crucial to maximizing structural and electronic interactions, which are essential for energy conversion and storage technologies. Hierarchically structured hybrids of ZnO with carbon nanotubes (CNTs) are an example of this co-operative behavior. ZnO is characterized by a wide band gap and large exciton binding energy and CNTs ensure very high electrical conductivity. In the present work, a 3-D construction based on an array of 1-D vertically aligned (VA) CNTs constitute the conductive substrate for the growth of ZnO semiconductor nanoparticles using a laser-assisted flow deposition method. The functional interaction at the nanoscale between both materials is demonstrated by the enhancement of the high resolved near band edge recombination which accounts for an almost three orders of magnitude increase when compared with the green spectral band. A rectifying behavior was found for the ZnO/VACNT system.